Aves colecionadas na localidade de Fazenda Caiuá (Paraná, Brasil) por Adolph Hempel, com discussão sobre a sua localizaç ão exata - Straube, Fernando C.; Willis, Edwin O. [UNESP]; Oniki, Yoshika (My University, 2002)
The region known as the pioneer north of Paraná State can be considered one of the most severely modified in southern Brazil, due to the colonization that started at the end of 19th century. In this little known region, seldom visited by traveler naturalists of the past, the collector Adolph Hempel obtained an important series of bird specimens that constitute, in many cases, the only - and last - information concerning the avifauna of this region. For several reasons, Fazenda Cayoá has been associated with the State of São Paulo, although it was an important center for coffee in the early 20th. century and is near the left bank of Rio Paranapanema, thus in the State of Paraná.
Birds collected in Fazenda Caiuá (Paraná, Brazil) by Adolph Hempel with a discussion of its exact location
Keywords: Adolph Hempel; Fazenda Caiuá; Paraná; São Paulo; Aves